Mapping of processes and risks in the digital transformation in metrology of ionizing radiation, a case study in X-rays air kerma calibration - Igor Fernando Modesto Garcia; Jeovana Santos Ferreira; Eric Matos Macedo; Marcos Vinicius Teixeira Navarro; José Guilherme Pereira Peixoto (Brazilian Journal of Radiation Sciences)
For the new metrological challenges of an increasingly digitized world, several countries are developing applications and infrastructure for Digital Calibration Certificates – DCC, researching the comparability of real and virtual measurements. Objective: to map the processes and risks related to the digital transformation of X-rays air kerma calibration. The Failure Mode and Effect Analysis - FMEA was used to quantify risks and is widely used in the aviation and automotive industry due to its reliability. The results presented a conceptual model for calibrating ionizing radiation quantities in the framework of new technologies and calibration 4.0 and comparing processes and risks. The conceptual model of calibration 4.0 comprises three main parts: a transmitter, the 4.0 communication network, and a receiver. Intelligent devices with configurations enable calibration data transfers by radio-frequency messaging in all these parts. Comparing risks in contemporary and calibration 4.0 processes, a slight reduction in the total risk can be observed. But new risks are unique to the 4.0 model, all with maximum severity, and how to mitigate them is still unknown. It is also possible to estimate that artificial intelligence and automation can significantly reduce measurement risks, identification, and error in the analysis and use of calibration certificates.